SABDA SEBAGAI SUMBER SPIRITUALITAS LITURGI : Berdasarkan Analisa Biblis-Liturgis atas Kisah Emaus (Luk. 24:13-35) - Pondaag, Stenly Vianny; Pongoh, Damianus; Wuritimur, Amrosius (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
The essay deals with Word of God as source of liturgical spirituality This paper aims to discover the spirituality of the Eucharistic celebration based on a biblical-liturgical analysis of the Emmaus Story (Luke 24:13-35). If we reconstruct the Emmaus story from a liturgical perspective, specifically the Eucharistic celebration, then the structure of the Eucharistic celebration becomes very clear. The biblical-liturgical analysis of the Emmaus Story shows that the Eucharist is a spiritual journey with the Risen Lord. God's presence is sometimes not recognized because we are covered by worries, anxieties, and unfulfilled hopes. The Emmaus Story also points us to two important structures of the Eucharistic celebration: the liturgy of the Word and the liturgy of the Eucharist. In the liturgy of the Word, Christ himself speaks and opens our hearts by explaining the contents of Scripture. In the Liturgy of the Eucharist, the Risen Christ allows himself to be known through the breaking of bread. The Eucharist is not only a celebration, but is directed towards the transformation of life that enables believers to become witnesses of Jesus' resurrection.